Implementasi Suri Tauladan Guru dalam Membentuk Akhlakul Karimah Murid di Lembaga Pesantren Al-Qur’an Darul Qur’an Walkutub Geger Bangkalan - Hadiri, Hadiri; Aliyah, Nelud Darajaatul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study discusses how the role of teacher role models is applied in forming noble morals (akhlakul karimah) in students at the Al-Qur'an Darul Qur'an Walkutub Islamic Boarding School, Geger Bangkalan. Using a descriptive qualitative method, this study evaluates how teachers provide examples and their influence on the formation of students' character. The findings of the study revealed that teacher role models are manifested through various aspects, such as the use of polite language, good behavior, and actions that reflect Islamic teachings. Teachers consistently apply moral values ​​in their daily interactions with students. Factors that support this success include the consistency of teacher attitudes and a supportive pesantren atmosphere. Meanwhile, the obstacles faced include the low discipline of some students and negative influences from outside the pesantren environment. As a recommendation, this study suggests ongoing teacher training, the implementation of a technology-based evaluation system, and strengthening cooperation with families and communities to maximize the process of forming students' akhlakul karimah.